Community-level socioeconomic inequalities in infants with poor fetal growth in Western Australia, 1984 to 2006 - Langridge, A.; Li, Jianghong; Nassar, N.; Stanley, F. (Elsevier, 2011)
pose: This study describes social and racial inequalities in poor fetal growth in Western Australia between 1984 and 2006. Methods: Multilevel multivariate logistic regression was used to investigate relative differences in fetal growth restriction between socioeconomic groups. Fetal growth restriction was defined as having a proportion of optimal birth weight corresponding to less than the 10th percentile for the population. Aboriginal (N = 50,395) and non-Aboriginal (N = 517,073) infants were analyzed separately. Results: There has been an overall decrease in the rate of poor fetal growth during the last 23 years, with a plateau reached in recent years. Aboriginal infants were significantly more likely to have fetal growth restriction than non-Aboriginal infants and social inequalities increased over time, particularly among non-Aboriginal infants. After stratifying by Aboriginality and accounting for important parental sociodemographic characteristics, the community-level socioeconomic gradient remained. Conclusions: This study highlights the misleading nature of observing aggregated rates of poor fetal growth that mask increasing inequalities, and the importance of monitoring trends by social and racial characteristics. It also highlights the concerning finding that almost all improvements in poor fetal growth have occurred in the least disadvantaged communities, with almost no change in the most disadvantaged communities, which is likely to result in further increases in social and racial inequalities.